Особливості огляду місця події під час розслідування корупційних злочинів у сфері службової діяльності та професійної діяльності, пов’язаної з наданням публічних послуг - Дорошенко, Ю. К.; Doroshenko, Yu. K.; Юлія Дорошенко (Юридична наука. - 2020. - № 9 (111). - С. 135-140, 2020)
Визначено, що під час розслідування корупційних злочинів у сфері службової діяльності та професійної діяльності, пов’язаної з наданням публічних послуг, слідчий переважно стикається з проведенням огляду місця події. Вміле проведення огляду місця події дає можливість одержати цінну орієнтуючу і доказову інформацію, необхідну для встановлення обставин, що підлягають доказуванню. Крім того, отримані при огляді відомості допомагають висувати обґрунтовані версії; планувати шляхи їхньої перевірки; визначати напрями досудового розслідування.

The purpose of the article is to determine the features of the inspection of the scene during the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services. The article analyzes the peculiarities of the inspection of the scene during the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services. It was emphasized that the investigative review is one of the most important investigative actions during the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services. It is emphasized that during the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services, the investigator is mainly faced with conducting an inspection of the scene of the incident. The inspection of the scene during the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services can be divided into three stages: preparatory, working, final. The preparatory stage of the inspection of the scene of the incident begins from the moment the investigator makes a decision to conduct it. It was concluded that during the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services, the investigator is mainly faced with conducting an inspection of the scene of the incident. A skillful inspection of the scene of the incident makes it possible to obtain valuable guiding and evidentiary information necessary to establish the circumstances to be proven. In addition, the information obtained during the review helps to put forward well-founded versions; to plan ways of checking them; determine directions of pre-trial investigation.

Определено, что при расследовании коррупционных преступлений в сфере служебной деятельности и профессиональной деятельности, связанной с предоставлением публичных услуг, следователь в основном сталкивается с проведением осмотра места происшествия. Умелое проведение осмотра места происшествия позволяет получить ценную ориентирующую и доказательную информацию, необходимую для установления обстоятельств, подлежащих доказыванию. Кроме того, полученные при осмотре сведения помогают выдвигать обоснованные версии; планировать пути их проверки; определять направления досудебного расследования.
Peculiarities of the scene review during the investigation of corruption crimes in the sphere of official activity and professional activity related to the provision of public services
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; корупція; corruption; коррупция; корупційні злочини; corruption crimes; коррупционные преступления; огляд місця події; inspection of the scene; осмотр места происшествия; службова діяльність; official activity; служебная деятельность; публічні послуги; public services; публичные услуги; професійна діяльність; professional activity; профессиональная деятельность; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; досудове розслідування; pre-trial investigation; досудебное расследование